A review on online intervention for anxiety disorder - Nur Atirah Mohd Haizir,; Ponnusamy Subramaniam,; Shazli Ezzat Ghazali,; Normah Che Din,; Noh Amit, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Anxiety Disorders share features of excessive fear and anxiety related behavioral disturbances. Diagnosis of Anxiety Disorders often leads to a high financial burden to the sufferers and economical lost to the society with high rates of health care costs and days on sick leave. Online intervention is seen as a good option to deal with anxiety issues. Therefore this paper aimed to review past studies on online intervention programs for anxiety related problems and its effectiveness. Eight studies from electronic databases PubMed, PsycINFO, MEDLINE, and CINAHL were identified. The findings suggest that an online intervention program can be effective in reducing anxiety symptoms. Several different psychological treatments for Anxiety Disorders exist, but Cognitive Behavioral Therapy (CBT) is the most used in online intervention program. Online program using CBT targeting Anxiety Disorders is commonly based on psychoeducation, cognitive restructuring, and relaxation. Additional interventions components often used in online intervention programs are problem-solving, worry exposure, mindfulness, and relapse prevention. In conclusion, the online interventions for Anxiety Disorders could serve as cost and time effective alternatives, but with certain considerations, especially on adherence towards the treatment.